Informed Consent Dalam Penanganan Pasien Gawat Darurat Di Puskesmas Kota Kediri Wilayah Selatan - Eri Puji Kumalasari (Universitas Muhammadiyah Surabaya, 2022)
Objective: Research Objectives: Knowing the importance of informed consent in handling emergency patients at the Kediri City Health Center in the South Region in 2021Methods: This study was descriptive to determine informed consent at the Kediri City Health Center in the South Region. Using a combined research method that is analytic with cross sectional approach and normative juridical. The study was conducted in January 2022. The population in this study was based on data from the Kediri City Health Center in the Southern Region. The data were processed to determine the level of intensity of informed consent at the research site.Results: Based on the results of the study, it is known that in the period of 2021 the informed consent rate at the Kediri City Health Center in the southern region occurred 13 cases of emergency and accidental deliveries. Where this number can be called high for emergency patients.Conclusion: Based on the results of the study, it can be concluded that to avoid the high mortality rate of emergency patients, in handling emergency patients, prior approval is not required, the most important thing is to save the life of a patient. This is in accordance with the applicable laws and regulations, namely Article 4 paragraph (1) of the Minister of Health Regulation Number 290/Menkes/Per/III/2008 concerning Approval of Medical Actions. Although here there is a conflict of norms among several rules regarding informed consent.